Retrospective evaluation of the relationship between admission variables and brain herniation in dogs (2010–2019): 54 cases. Issue 1 (5th October 2021) - Her, Jiwoong; Yanke, Amy B.; Gerken, Katherine; Yoon, Jin; Peters, Ashley Antonia; Hofmeister, Erik; Bacek, Lenore M.; Kuo, Kendon W.
Abstract: Objective: To document the admission systolic blood pressure (SBP), heart rate (HR), and modified Glasgow coma scale (MGCS) score in dogs with and without brain herniation and to determine their relationship with brain herniation. Design: Retrospective study between 2010 and 2019. Setting: University veterinary teaching hospital. Animals: Fifty‐four client‐owned dogs with brain herniation and 40 client‐owned dogs as a control group, as determined on magnetic resonance imaging. Interventions: None. Measurements and Main Results: SBP, HR, MGCS score, and outcome were extracted from medical records. MGCS score was retrospectively calculated based on initial neurological examination in dogs with adequate available information. Dogs with brain herniation had a significantly higher SBP ( P = 0.0078), greater SBP–HR difference ( P = 0.0006), and lower MGCS score ( P < 0.0001) compared to control dogs. A cutoff value of an SBP ≥ 178 mm Hg, SBP–HR ≥ 60, and MGCS score ≤ 14 each provides a specificity of 90%–98%. A combination of an SBP > 140 mm Hg and HR < 80/min provided 24% sensitivity and 100% specificity to diagnose dogs with brain herniation ( P < 0.0001). Conclusions: A high SBP, a greater difference between SBP and HR, a combination of higher SBP and lower HR, and a low MGCS score were associated with brain herniation in dogs presenting with neurological signs upon admission. Early recognition of these abnormalities may help veterinarians to suspect brain herniation and determine timely treatment.